2022
DOI: 10.33899/ijvs.2021.128475.1581
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenic analysis of Anaplasma spp. in small ruminants from Sulaymaniyah governorate, Iraq

Abstract: Anaplasma spp. are significant arthropod-borne bacteria globally, but documented information about anaplasmosis in small ruminants in the north of Iraq is insufficient. Hence, this study was conducted to determine the prevalence of Anaplasma spp. and identify sheep and goat tick vector populations in Sulaymaniyah Governorate, north Iraq. The study population consisted of 470 sheep and 145 goats from 45 livestock farms in 10 geographical locations of Sulaymaniyah Governorate. The study was accomplished from Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…To our knowledge, A. ovis has never been detected in goats in Egypt. Recently, some studies have reported goats infected with A. ovis in Iraq [ 48 ], Thailand [ 49 ], and Bangladesh [ 50 ]. Likewise, we found that buffaloes were positive for A. platys (GenBank: OL721670).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, A. ovis has never been detected in goats in Egypt. Recently, some studies have reported goats infected with A. ovis in Iraq [ 48 ], Thailand [ 49 ], and Bangladesh [ 50 ]. Likewise, we found that buffaloes were positive for A. platys (GenBank: OL721670).…”
Section: Discussionmentioning
confidence: 99%
“…Information Concerning age, gender, origin was collected.. For each animal, Blood was collected (with anticoagulants)from each animal and the blood was separated to obtain plasma and stored at -20°C for subsequent tests. (11,12,13). In addition, nasal swab samples were taken from animals showed respiratory signs.…”
Section: Study Animals and Samples Collectionmentioning
confidence: 99%